Von Willebrand disease type 1 mutation p.Arg1379Cys and the variant p.Ala1377Val synergistically determine a 2M phenotype in four Italian patients. (26th October 2016) - Pagliari, M. T.; Baronciani, L.; Stufano, F.; Garcia‐Oya, I.; Cozzi, G.; Franchi, F.; Peyvandi, F.
Abstract : Introduction: We characterized five patients affected with von Willebrand disease (VWD) carrying the p.Arg1379Cys mutation. One was diagnosed as VWD type 1 and four as type 2M. The 2M patients also have the variant p.Ala1377Val in cis with p.Arg1379Cys. Aim: To evaluate the role of p.Ala1377Val and p.Arg1379Cys von Willebrand factor (VWF) variants to explain patients' phenotype. Methods: Conventional phenotype tests were used to evaluate patients' plasma and platelets. Direct sequence analysis of exon 28 was carried out. The allele frequency of p.Ala1377Val was evaluated using online database. pcDNA3.1‐VWF‐WT and mutant (A1377V, R1379C and A1377V‐R1379C) expression vectors were transiently transfected in HEK293 cells. The capacity of WT and mutant recombinant (r)VWF (along with patients' plasma VWF) to bind glycoprotein Ibα (GpIbα) were evaluated, using two ELISA assays. One with a wild‐type (WT) recombinant (r)GpIbα at increasing ristocetin concentrations (from 0 to 1.50 mg mL −1 ) and the other with a gain‐of‐function mutant rGpIbα (VWF:GPIbM). Results: The substitution c.4130C>T (p.Ala1377Val) was reported as rare variant in online databases. At 0.25 mg mL −1 of ristocetin, WT, A1377V and R1379C showed 6, 7.5 and 12‐fold increased binding to rGpIbα, respectively. A1377V‐R1379C rVWF showed no increased binding to rGpIbα at the same ristocetin concentration and reached the highest binding, of only 3‐fold increased, at 1.50 mg mL −1 of ristocetin. The VWF:GPIbM showed strongly reduced values for the A1377V‐R1379C rVWF and the 2M patients' plasma. Conclusion: Our study showed that the presence of both p.Ala1377Val and p.Arg1379Cys mutations (synergistic effect) abolishes the binding of rVWF to rGpIbα, explaining patients' 2M phenotype.